IMF Survey : Volume 28, Issue 17. (IMF Survey; IMF Survey, 1999)
The rationale for IMF lending to Russia has been widely questioned, as have the record of earlier programs and the use made of previous IMF loans. In the following article, John Odling-Smee, Director of the IMF's European II Department, explains that the resumed lending was fully justified to support Russia's most recent economic policies.